YELLOW OUTSIDE, WHITE INSIDE: NEGOTIATING RACHEL CHU’S IDENTITY IN JON M. CHU’S CRAZY RICH ASIANS - Rifah Inayati; Diva Wenanda; Diah Ikawati Ayuningtias (Journal of Arts and Education, 2022)
Crazy Rich Asians (2018), a film by Jon M. Chu is one of many films that raise this topic as the main theme of the story. This film tells about the life of a Chinese American woman, first generation, who was born and grew up in New York, the United States. This research is intended to elaborate how this movie portrays Rachel’s identity as a form of negotiation and why Rachel’s identity becomes problematic only when she met Nick’s family. By conducting descriptive qualitative method, this research uses only some dialogues and narration taken from Crazy Rich Asians film script as the source of data. Since the intention of this research is to analyze the identity negotiation between two cultures, therefore this research is conducted under postcolonial theory. The result of the study shows that although Rachel still hold on the Chinese culture as her ancestor’s culture, it turns out that American values has influenced her a lot in making decision. It leads to her conflict with Nick’s mother since Eleanor hold on Chinese traditional cultures. This research concludes that negotiation showed by Rachel in the movie is needed to do in order to be accepted by both of the cultures although it still leads to some conflict.